Economic Growth and Human Development: a Comparative Analysis between Mexico and Costa Rica in the Framework of the 2030 Agenda - Lara Martínez, Octavio Rolando (2026)
This article aims to comparatively analyze the relationship between economic growth and human development in Mexico and Costa Rica within the framework of the 2030 Agenda during the period 1990–2023. It seeks to determine the extent to which economic growth has translated into sustained improvements in human development in both countries. The methodology employed is a documentary study with empirical analysis using linear regression, performed with SPSS software. Official statistics from the United Nations Development Programme (UNDP), the World Bank, and the Economic Commission for Latin America and the Caribbean (ECLAC) were processed. The results indicate that, although both countries have made progress in terms of growth and social indicators, Costa Rica demonstrates a greater capacity to transform economic growth into sustained human development. The study shows that the quality of social policy, investment in human capital, and institutional coherenceaffect the transformation of economic development into well-being key issues to address when planning a development trajectory for Latin America.